A Semi-parametric NHPP-based Software Reliability Modeling with Local Polynomial Debug Rate - Li, Siqiao; Dohi , Tadashi; Okamura, Hiroyuki (Journal of Reliability and Statistical Studies, 2023)
In this paper, we propose a new non-homogeneous Poisson process (NHPP) based software reliability model (SRM), where the software debug rate is given by a local polynomial function. The main feature of this semi-parametric SRM is to control the goodness-of-fit by changing the polynomial degree. Numerical examples with 16 actual software development project data are devoted to comparing our SRM with the well-known existing NHPP-based SRMs in terms of goodness-of-fit and predictive performances.